PENERAPAN MODEL COOPERATIVE SCRIPT DENGAN MEDIA GRAFIS DALAM PENINGKATANMOTIVASI DAN HASIL BELAJAR IPS PADA SISWA KELAS IV SDN 4 BUMIREJO TAHUN AJARAN 2015/2016 - Indrawati, Rina (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Cooperative ScriptModel Using Graphic Media in Improving Motivation and Learning Outcomes for the Fourth Grade Students of SD Negeri 4 Bumirejo in the Academic Year of 2015/2016.The objectives of this research are to improve motivation and learning outcomes of students. This research is conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection.The results of this research showed that the percentage of students? motivation in the first cycle 71.94% ,in the second cycle 82.22%, and in the third cycle 91,94%.The percentage of learning from students in the first cycle 71.05%, in the second cycle 84.74%, and in the third cycle 93.28%. The conclusion of this research is the application of cooperative script model using graphic mediacan improve motivation and learning outcomes of students for the fourth grade students of SD Negeri 4 Bumirejo in the academic year of 2015/2016. Keywords: Cooperative Script, graphic media, social science learning outcomes Abstrak: Penerapan Model Cooperative Script dengan Media Grafisdalam Peningkatan Motivasi dan Hasil Belajar IPS pada Siswa Kelas IV SDN 4 Bumirejo Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan motivasi dan hasil belajar siswa. Penelitian dilaksanakan dalam tiga siklus dan tiap siklus terdiri dari 2 pertemuan yang meliputi perencanaan, pelaksanaan, observasi, refleksi. Hasil penelitian menunjukkan motivasi belajar siswa pada siklus I-III yaitu 71,94%, 82,22%, dan 91,94%. Persentase jumlah siswa yang mencapai KKM pada siklus I- III yaitu 71,05%, 84,74%, dan 93,28%. Simpulan penelitian ini adalah penerapan model cooperative script dengan media grafis dapat meningkatkan motivasi dan hasil belajar IPS pada siswa kelas IV SDN 4 Bumirejo tahun ajaran 2015/2016. Kata Kunci: Cooperative Script, Media Grafis, Hasil Belajar IPS